Fractal perspective on dynamics of dark matter and dark energy interactions - Priyanka, T.M.C.; Gowrisankar, A.; Banerjee, Santo (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, the dynamics of intricate chaotic attractors of the nonlinear system modeling the dark matter and dark energy interactions is studied indulging fractal–fractional operator in the Caputo sense. The constructed strange attractors witness that the dynamics of the universe components is dominated by the fractal properties. The fractional entropies stemmed from the classical entropy are estimated with fractal parameter and graphically portrayed to measure the randomness of the dynamic variables associated with the proposed dynamical system.
Keywords: dark matter; dark energy; dynamics; fractal–fractional operator; entropy